Pengelolaan Keuangan Keluarga Pedagang Etnis Cina - Suhartini, Dwi; Ardhian Renanta, Jefta (Jurnal Riset Ekonomi dan Bisnis, 2007)
Chinese of through Kya-Kya Kembang Jepun, not only have been able to realize an area which intern for its community, but have also been utilized by as public space of wide society. As New Comer, their role as merchant in boga and non-boga by taking a small area corner of town Surabaya, namely Kembang Jepun and label by the name of Kya-Kya  having that meaning is Jalan-Jalan. This ethnical have proved that their arrival in this country, not only merely freeload, but they also show in the field of commerce. As merchant, practically always more uppermost from all economics perpetrator which have background from different ethnical. Those who more preeminent in commerce area, inviting big question mark why and how them can create the excellence, in the middle of middle as minority ethnical.This research aim to know about the ethnical merchant of Chinese in Kya-Kya manage the finance so that earn more pre-eminent in the field of commerce. Where method used to dig and explain the this family management research method qualitative.This research that ethnical of Chinese in Kya-Kya all family member in planning management, commissioned to though make the finance note of most is wife, but husband dominant in make decision an everything related to family finance. They develop the behavior from original culture they hold the firmness. From research found the fact that cultural facet, belief, experience and even religion of background of character forming have all ethnical merchant of Chinese in Kya-Kya Kembang Jepun in managing family finance.Keywords: Ethnical, Chinese, Tradition, Finance, Family